Fiscal Capacities of Large Cities in Croatia – Financial Support for Smart Cities - Hodžić, Sabina; Paleka, Hana (Naše gospodarstvo/Our economy, 2020)
In a dynamic market, the city has become a main source of competitiveness, along with financial and economic benefits. Due to the processes of digitalization, a new concept has been developed, namely smart cities. This concept delivers economic and financial potential, not only to cities, but also to urban and local economic development. Therefore, to ensure the establishment of this concept, local government units, i.e., cities, need to have enough financial resources. In addition, the fiscal capacity of their local budgets should be sufficient. The objective of this paper is to evaluate the fiscal capacity of large cities in Croatia over the 2016-2018 period, as well as to present the financial support through funding schemes for the establishment of smart cities. After calculating the level of fiscal capacity of large cities, the analysis revealed interesting results. Only four large cities (Split, Rijeka, Zadar and Pula) achieved positive fiscal capacity in the observed period. This provides evidence of fiscal performance and fiscal capacity for the establishment of smart cities. This concept will enhance the quality of life, stimulate economic growth, sustain local government budgets and create new value for both investors and the local population.
Keywords: local government; smart cities; fiscal capacity; local economic development